Inhibition of Hepatitis B virus using helper-dependent adenoviral vectors expressing pri-miRNAs from liver-specific MTTR promoter - Mdunyelwa, Anele (My University, 2017)
Approximately 240 million people are estimated to be chronic carriers of hepatitis B virus (HBV), placing them at high risk for complications like hepatocellular carcinoma (HCC) and cirrhosis. Infection with the virus is predominantly high in sub Saharan Africa, East and Southeast Asia. Current treatments are limited by the emergence of viral resistance and adverse side effects. These challenges prompted development of new therapy for HBV. The application of RNA interference (RNAi) as a form of treatment has shown successful HBV silencing. However, safe and efficient delivery of anti-HBV sequences remains a challenge. Recombinant adenoviruses (Ads) have a natural tropism for the liver, making them suitable for anti-HBV sequence delivery. Their use in gene therapy is limited by their ability to induce the innate and adaptive immune response, thus leading to diminished transgene expression. To overcome immune stimulation, third generation helper-dependent adenoviral vectors (HDAds), which are devoid of all their viral coding sequences, were developed. This study investigated the use of HDAds expressing primary micro RNA (pri-miRNA) sequences from the liver-specific MTTR promoter with the aim of inhibiting HBV replication. The anti-HBV pri-miRNA expression cassettes were successfully cloned into the adenoviral bearing genome and used for HDAd production. Infection of liver derived cell line with these HDAds resulted in efficient pri-miRNA expression and processing into expected guide sequences. This was accompanied by a significant inhibition of HBV replication. Injection of the HDAds into mice resulted in efficient liver transduction and no significant induction of the inflammatory response or liver toxicity. However, as a result of high levels of HBV replication markers produced in the transgenic mice used, this did not translate into significant HBV replication inhibition. This study therefore highlights the safety and therapeutic potential of HDAds against HBV infection. To demonstrate HBV gene silencing in vivo, transgenic mice expressing HBV replication markers will be used.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment with the requirements for the degree of Master of Science in Medicine Johannesburg, 2017.
Keywords: Hepatitis B virus; RNA Interference; MicroRNAs